2015
DOI: 10.4244/eijv10i12a245
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and clinical comparisons of intravascular ultrasound- versus angiography-guided drug-eluting stent implantation for patients with chronic total occlusion lesions: two-year results from a randomised AIR-CTO study

Abstract: The IVUS-guided stenting of the CTO lesion was associated with less LLL and a lower incidence of "in-true-lumen" stent restenosis. Additional study is required to identify the clinical benefit of the IVUS-guided procedure for CTO lesions. [ChiCTR-TRC-10000996].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 26 publications
2
109
1
3
Order By: Relevance
“…However, in two randomized trials, IVUS use was not associated with a reduction of contrast load [18,19]. Although in our study, less contrast was required in IVUS guided CTO PCI attempts, this did not result in lower incidence of contrast induced nephropathy.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…However, in two randomized trials, IVUS use was not associated with a reduction of contrast load [18,19]. Although in our study, less contrast was required in IVUS guided CTO PCI attempts, this did not result in lower incidence of contrast induced nephropathy.…”
Section: Discussioncontrasting
confidence: 56%
“…However, this latter study was underpowered because of low events rate observed in both groups. In the AIR-CTO trial, there were no differences in the composite MACE and in the individual component of clinical adverse events between the 2 study groups at 1-and 2-year follow-ups [18]. Therefore, the impact of IVUS guided CTO PCI on clinical outcome is still not yet well established; further studies are needed to better assess it.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Intravascular imaging including intravascular ultrasound (IVUS) and optical coherence tomography (OCT) represent two techniques that provide essential information on preprocedural lesion characteristics (i.e., lesion severity, landing zone, and plaque composition) and the result after stent implantation (i.e., stent expansion and eccentricity, strut apposition, lesion coverage, tissue protrusion, and dissections). A total of 11 randomized controlled trials investigated the effect of IVUS-guided PCI with mixed results (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Of note, studies including patients with an increased complexity [i.e., chronic total occlusion (CTO) or lesion length >28 mm] demonstrated a consistent benefit of IVUS-guided PCI as compared with angiography, mainly driven by a reduction of repeat revascularization for restenosis (MACE at 1 year: CTO-IVUS, 2.6% vs. 7.1%, P=0.035; IVUS-XPL, 2.9% vs. 5.8%, P=0.007) (1,2).…”
Section: What Was Known Before Ilumienmentioning
confidence: 99%